Penetration of 0.3% ciprofloxacin, 0.3% ofloxacin, and 0.5% moxifloxacin into the cornea and aqueous humor of enucleated human eyes - G.C.M. Silva; V.A.P. Jabor; P.S. Bonato; E.Z. Martinez; S.J. Faria-e-Sousa (Brazilian Journal of Medical and Biological Research)
We aimed to quantify the penetration of ciprofloxacin, ofloxacin, and moxifloxacin into the cornea and aqueous humor of cadaver eyes. A total of 60 enucleated eyes, not eligible for corneal transplantation, were divided into three groups and immersed in commercial solutions of 0.3% ciprofloxacin, 0.3% ofloxacin, or 0.5% moxifloxacin for 10 min. Whole corneas and samples of aqueous humor were then harvested and frozen, and drug concentrations analyzed by liquid chromatography tandem mass spectrometry. The mean corneal concentration of moxifloxacin was twice as high as ofloxacin, and the latter was twice as high as ciprofloxacin. The mean concentration of moxifloxacin in the aqueous humor was four times higher than the other antibiotics, and the mean concentrations of ciprofloxacin and ofloxacin were statistically similar. The amount of drug that penetrated the anterior chamber after a 10-min immersion was far below the safe limit of endothelial toxicity of each preparation. Moxifloxacin demonstrated far superior penetration into the cornea and anterior chamber of cadaver eyes compared to ciprofloxacin and ofloxacin. One should not expect endothelial toxicity with the commercial eye drops of ciprofloxacin, ofloxacin, and moxifloxacin that reach the anterior chamber through the cornea.